Interdisciplinary consensus of virtual monochromatic dual-energy CT images: is there discrepancy in preferred photon energy between surgeons and radiologists for the assessment of non-unions?. Issue 6 (June 2020) - Wellenberg, R.H.H.; Donders, J.C.E.; Guitton, T.G.; Streekstra, G.J.; Kloen, P.; Maas, M.
Abstract : AIM: To investigate possible differences between surgeons and radiologists in selecting optimal photon energy settings from a set of virtual monochromatic dual-energy computed tomography (CT) images for the assessment of bone union in patients with a suspected non-union of the appendicular skeleton. MATERIALS AND METHODS: Fifty patients suspected of having bone non-union after operative fracture treatment with a variety of fixation implants were included. Patients were scanned on a dual-source CT machine using 150/100-kVp. Monochromatic images were extracted at 70, 90, 110, 130, 150, and 190 keV. Images were reviewed by 159 orthopaedic trauma surgeons and 12 musculoskeletal radiologists in order to select the best and worst energy setting to assess bone union. Furthermore, a confidence score (1–4) was given in selecting the best and worst setting to assess bone union. RESULTS: Monochromatic 190 keV images were selected most frequently as the optimal energy in titanium (34.8%), stainless steel (40%), and combined implants of stainless steel and titanium (40.5%). Confidence scores and average optimal energies were higher and average worst energies were lower for radiologists compared to surgeons in all hardware ( p< 0.05). Differences in optimal energy were not statistically significant for different alloys or type of fixation implant in both groups. CONCLUSIONS: In both observer groups, 190 keV images were selected most frequently as the optimal energy to assess bone union in patients with a suspected non-union of the appendicular skeleton with hardware in situ. On average, musculoskeletal radiologists selected higher optimal and lower worst energy settings and were more confident in selecting both energy settings than orthopaedic trauma surgeons. Highlights: 190 keV images were most frequently selected as optimal keV to assess bone union. Preferences regarding the optimal keV were similar in surgeons and radiologists. Alloy or implant type did not affect optimal keV selection in both observer groups.